Pretrial as Supervisory Mechanism for Protecting Suspects' Human Rights - Tongat, Tongat; Md Said, Muhamad Helmi; Rozah, Umi (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2026)
Although coercive measures in the investigative and prosecutorial processes are essentially legitimate, the line between necessary detention and violations of individual freedoms and human rights is often blurred in practice. Therefore, a control mechanism is essential. This paper aims to analyse two main issues: first, the use of pretrial as a mechanism for monitoring the implementation of suspects' human rights protection during the investigation and prosecution process; and second, the need to consider material aspects in pretrial. Using conceptual, legislative and comparative approaches, this paper reaches at least two conclusions. Firstly, as its focus is limited to the formal procedural process, the pretrial process, as set out in Law Number 8 of 1981 concerning the Criminal Procedure Code, has failed to fulfil its function as a control mechanism for ensuring the protection of suspects' human rights during the investigation and prosecution process. Secondly, the absence of provisions for examining material aspects in pretrial further confirms that it is unable to control the use of coercive measures in the investigative and prosecutorial processes